The outcasts : a novel - Kent, Kathleen, 1953- (New York : Little, Brown and Company, 2013)
"A taut, thrilling adventure story about buried treasure, a manhunt, and a woman determined to make a new life for herself in the old west. It's the 19th century on the Gulf Coast, a time of opportunity and lawlessness. After escaping the Texas brothel where she'd been a virtual prisoner, Lucinda Carter heads for Middle Bayou to meet her lover, who has a plan to make them both rich, chasing rumors of a pirate's buried treasure. Meanwhile Nate Cannon, a young Texas policeman with a pure heart and a strong sense of justice, is on the hunt for a ruthless killer named McGill who has claimed the lives of men, women, and even children across the frontier. Who--if anyone--will survive when their paths finally cross? As Lucinda and Nate's stories converge, guns are drawn, debts are paid, and Kathleen Kent delivers an unforgettable portrait of a woman who will stop at nothing to make a new life for herself. "--
"It's the 19th century on the Gulf Coast, a time of opportunity and lawlessness. After escaping the Texas brothel where she'd been a virtual prisoner, Lucinda Carter heads for Middle Bayou to meet her lover, who has a plan to make them both rich, chasing rumors of a pirate's buried treasure. Meanwhile Nate Cannon, a young Texas policeman with a pure heart and a strong sense of justice, is on the hunt for a ruthless killer named McGill who has claimed the lives of men, women, and even children across the frontier. Who--if anyone--will survive when their paths finally cross? As Lucinda and Nate's stories converge, guns are drawn, debts are paid, and Kathleen Kent delivers an unforgettable portrait of a woman who will stop at nothing to make a new life for herself"--
Keywords: Brothels -- Fiction; Travelers -- West (U.S.) -- History -- 19th century -- Fiction; FICTION / Historical; FICTION / Westerns; FICTION / Suspense; FICTION / Romance / Suspense; Gulf Coast (La.) -- History -- 19th century -- Fiction; Adventure fiction; Romance fiction; Western fiction